Carvacrol after status epilepticus (SE) prevents recurrent SE, early seizures, cell death, and cognitive decline. (13th January 2017) - Khalil, Aytakin; Kovac, Stjepana; Morris, Gareth; Walker, Matthew C.
Summary: Objective: Carvacrol is a naturally occurring monoterpenic phenol that has been suggested to have an action at transient receptor potential cation subfamily M7 (TRPM7) channels, γ‐aminobutyric acid (GABAA receptors, and sodium channels, and has been shown to be antiinflammatory. Carvacrol is neuroprotective in models of cerebral ischemia in vivo and in vitro, probably through its action at TRPM7 channels. We therefore aimed to determine the effect of carvacrol on status epilepticus (SE), chronic epilepsy, cell death, and post‐SE cognitive decline. Methods: We performed long‐term, continuous wireless electroencephalography (EEG) monitoring in vivo in rats who underwent perforant path stimulation (PPS) to induce SE and were then randomized to treatment with carvacrol or saline. We also evaluated TRPM7 receptor expression and quantified seizure‐induced cell death. The alternating T‐maze paradigm was used to assess memory function. Results: Immunostaining showed that TRPM7 channels are widely expressed in neurons within the hippocampus. We found that carvacrol inhibited recurrent SE and early seizures in vivo, but had no detectable effect in the hippocampus on paired‐pulse inhibition or the fiber volley, indicating that it was not acting through sodium channel inhibition or GABA receptors. Although the development and severity of chronic epilepsy were not altered by carvacrol, cognitive decline was significantly improved in animals treated with carvacrol. In keeping with preserved memory functions in animals treated with carvacrol, carvacrol had a protective effect against SE‐induced cell death in CA1 and hilus, the hippocampal regions most affected by cell loss in the PPS epilepsy model. Significance: Carvacrol, a naturally occurring inhibitor of TRPM7 channels, is a novel, promising treatment to prevent early recurrence of SE, SE‐related neuronal damage, and cognitive decline.